Serious Infections in Patients Receiving Ibrutinib for Treatment of Lymphoid Cancer. (27th April 2018) - Varughese, Tilly; Taur, Ying; Cohen, Nina; Palomba, M Lia; Seo, Susan K; Hohl, Tobias M; Redelman-Sidi, Gil
Abstract: Background: Ibrutinib is a Bruton tyrosine kinase inhibitor that is used for the treatment of lymphoid cancers, including chronic lymphocytic leukemia, Waldenström macroglobulinemia, and mantle cell lymphoma. Several case series have described opportunistic infections among ibrutinib recipients, but the full extent of these infections is unknown. We sought to determine the spectrum of serious infections associated with ibrutinib treatment. Methods: We reviewed the electronic medical records of patients with lymphoid cancer at Memorial Sloan Kettering Cancer Center who received ibrutinib during a 5-year period from 1 January 2012 to 31 December 2016. Serious infections were identified by review of the relevant microbiology, clinical laboratory, and radiology data. Risk factors for infection were determined by means of univariate and multivariate analyses. Results: We analyzed findings in 378 patients with lymphoid cancer who received ibrutinib. The most common underlying cancers were chronic lymphocytic leukemia and mantle cell lymphoma. 84% of patients received ibrutinib as monotherapy. Serious infection developed in 43 patients (11.4%), primarily during the first year of ibrutinib treatment. Invasive bacterial infections developed in 23 (53.5%) of these patients, and invasive fungal infections (IFIs) in 16 (37.2%) .The majority of patients with IFIs during ibrutinib therapy (62.5%) lacked classic clinical risk factors for fungal infection (ie, neutropenia, lymphopenia, and receipt of corticosteroids). Infection resulted in death in 6 of the 43 patients (14%). Conclusions: Patients with lymphoid cancer receiving ibrutinib treatment are at risk for serious infections, including IFIs. Abstract : We reviewed the spectrum of serious infections among 378 patients with lymphoid cancer who received treatment with ibrutinib, a Bruton tyrosine kinase inhibitor. Serious infection occurred in 43 (11.4%) of the patients, invasive fungal infections in 16 (37.2%).